2009
DOI: 10.1007/s11270-009-0188-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Microbial Methane Oxidation Efficiencies in Two Experimental Landfill Biocovers Using Stable Isotopes

Abstract: Stable isotope analyses were performed on gas samples collected within two instrumented biocovers, with the goal of evaluating CH 4 oxidation efficiencies (f 0 ). In each of the biocovers, gas probes were installed at four locations and at several depths. One of the biocovers was fed with biogas directly from the waste mass, whereas the other was fed through a gas distribution system that allowed monitoring of biogas fluxes. While the f 0 values obtained at a depth of 0.1 m were low (between 0.0% and 25.2%) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 27 publications
(49 reference statements)
3
29
1
Order By: Relevance
“…The higher diffusion coefficient in the porous medium (5.54 × 10 −6 m 2 s −1 ) could facilitate isotopic fractionation by diffusion. Measurements in this study showed no correlation between diffusion coefficients and α diff , but might show a different relationship with higher concentration gradients as found in landfill habitats where CH 4 concentrations up to 60 % are found at the bottom of cover soils (Cabral et al, 2010).…”
Section: Analysis Of Soil Gas Diffusivity and Isotopic Fractionation contrasting
confidence: 76%
See 2 more Smart Citations
“…The higher diffusion coefficient in the porous medium (5.54 × 10 −6 m 2 s −1 ) could facilitate isotopic fractionation by diffusion. Measurements in this study showed no correlation between diffusion coefficients and α diff , but might show a different relationship with higher concentration gradients as found in landfill habitats where CH 4 concentrations up to 60 % are found at the bottom of cover soils (Cabral et al, 2010).…”
Section: Analysis Of Soil Gas Diffusivity and Isotopic Fractionation contrasting
confidence: 76%
“…GPPTs are not easily applicable at sites with low oxidation rates and high water saturation (Gomez et al, 2008;Urmann et al, 2007), such as tundra wetlands, and have only been successfully applied in near-surface soils with a cylinder driven 50 cm into the soil (Nauer and Schroth, 2010). Furthermore, mass balance calculations using loading and surface flux measurements to determine the fraction of oxidized CH 4 , e.g., in biofilters or landfill cover soils (Powelson et al, 2007;Cabral et al, 2010;Gebert et al, 2003), are difficult to apply in wetlands since loading rates cannot be quantified in these open systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of δ 13 C-CO 2 in the CO 2 that arises from CH 4 oxidation is primarily affected by fractionation during the CH 4 oxidation process, and less dependent on the relative 13 C abundance in the source CH 4 . The CO 2 arising from CH 4 oxidation is highly depleted in 13 C and therefore typically exhibits a highly negative value of δ 13 C-CO 2 (Börjesson et al, 2001;Cabral et al, 2010;Chanton et al, 2011a;Liptay et al, 1998a;Widory et al, 2012a). …”
Section: Isotope Analysismentioning
confidence: 99%
“…Stable carbon isotopes have proven to be one of the most popular methods to estimate CH4 oxidation efficiency in cover soil systems over the last two decades (Bergmaschi and Harris, 1995, Chanton and Liptay, 2000, Liptay et al, 1998, Cabral and Capanema, 2012, Cabral et al, 2010, Widory et al, 2012. Liptay et al (1998) proposed that a landfill was an open system, as migrating gas reaches a branch point, where CH4 can be oxidised by methanotrophs or emitted to the atmosphere via gas transport, this can be expressed as:…”
Section: Introductionmentioning
confidence: 99%